Effect of Artemisia vulgaris Supplementation on Zebrafish Embryo Under Heat Stress Condition during In Vitro Culture - Tuska, Habib Syaiful Arif; Khamalt, Nursalsabila; Lesmana, Muhammad Arfan; Yesica, Reza; Hendrawan, Viski Fitri; Budiono; Residiwati, Gretania (Universitas Airlangga, 2024)
Background: Artemisia vulgaris contains flavonoids, which play a vital role in counteracting free radicals. Purpose: To determine the effect of Artemisia vulgaris extract supplementation on embryo development, heart rate and survival of zebrafish under heat stressed and non-heat stressed conditions. Methods: The research used a completely randomized design. Zebrafish embryos (n=240) were divided into heat stressed (36°C) and non-heat stressed (28°C) groups, while for each group were divided into three subgroups, namely T1/control (without Artemisia vulgaris supplementation); and supplemented group T1 and T2, with 2 µL and 4 µL of Artemisia vulgaris supplementation, respectively. The efficacy of Artemisia vulgaris supplementation was determined by observing the embryo development, heart rate, and survival rate of zebrafish up to 96 hours post fertilization (hpf). Results: The development of zebrafish embryos under heat stressed treated with Artemisia vulgaris extract gave the same quality as the control treatment without heat stressed exposure. Zebrafish embryos exposed to heat stressed with 4 µL Artemisia vulgaris supplementation gave the highest survival rate on the heat stressed group. Artemisia vulgaris supplementation improved the heart rate of zebrafish exposed to heat stressed as in the non-heat stressed group. Conclusion: Artemisia vulgaris extract can reduce the detrimental effects of heat stressed induction on zebrafish embryos, as evidenced by the improvement in embryonic development, heart rate, and survival rate of zebrafish embryos after supplementation.